Digital privacy and personal, social and civic agency: refugees' experiences - Voigts, Matthew (2020)
This dissertation explores how refugees in Europe and the UK manage privacy on social media. It aims, firstly, to empirically qualify if and how privacy supports individual, social and civic benefits with which it has been associated in theoretical literature and popular concern. Secondly, it connects these discussions on privacy to digital anthropological discussions of globally-situated social media use and an emerging multi-disciplinary literature on refugees’ social media use which have grown concurrently since the 2015 ‘refugee crisis’. The research was conducted through in-depth interviews with 23 refugees, asylum seekers, and other individuals from countries in conflict; participant-observation in eight migration-related NGOs; and ethnographic relationship building. The project was primarily conducted in the East Midlands of the UK. The methodology and theoretical approach draws from digital and existential anthropology.